An Experimental Study of Teaching Vocabulary by Using Hyponymy Games on the Seventh Grader F MTs Syech Ibrahim Payakumbuh - Fadilla Taslim (AT-TA'LIM, 2014)
Language is an effective tool to get communication, interaction, and information about other people, society and other groups. Whenever people think about language, they usually think of mastering vocabulary. Mastering vocabulary means that they know all the words in the language which we use. In this research, the writer would like to carry out the research under title “An Experimental Study of Teaching Vocabulary by Using Hyponymy Games on the Seventh Grader of MTs Syech Ibrahim Payakumbuh. It was quasi experimental method. The population was all of the seventh grader at Seventh Grader of MTs Syech Ibrahim Payakumbuh. But, the writer just took one class as the sample. The objects of the study was the seventh grade of 7c class. From the result of statistic calculation, it is obtained the value of to is 8,9 and tt is 2,64. So tott. The comparison between t-score with t-table (2,64 8,9). It means that hypothesis of the research is accepted, or there is significant difference between the results of teaching vocabulary through hyponymy games for the Seventh Grader of MTs Syech Ibrahim Payakumbuh. Copyright © 2014 by Al-Ta'lim All right reserved